Use of Zinc Oxide Solution as an Alternate Contrast Medium for Computed Tomography Imaging of Rabbit’s Heart, Kidney, and Liver - Ahmed Salman Jassim; Muhammed Mizher Radhi; Zainab Oun Ali (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: A new chemical compound of zinc oxide (ZnO) solution was used as a suitable an alternativecontrast agent in computed tomography scan (CT-Scan). The choosing of ZnO solution has distinct inelectrochemical study in the blood electrolyte. Results: From the results ZnO molecules in the blood mediaacts as an anti-oxidizing reagent that cyclic voltammogram result has reduction current peak at potential of-0.75 volt, while the using in routine contrast media in CT-scan is iodine compound; they have an anodicpeak in the blood medium at +1 volt. Additionally, iodine compounds have many problems through using forthe patients, but the current using in CT-Scan diagnosis are Iodine compounds for this purpose. Conclusions:the good alternative contrast medium using in the CT-Scan without any side effects and high resolution ofimaging which increased the Hounsfield unit (HU) values for rabbit’s organs (heart, kidney, and liver),compared with other cases through using the routine Iodine contrast media in the same doses.